Convergent Versus Sequential Protein Synthesis: The Case of Ubiquitinated and Glycosylated H2B1. Issue 42 (16th June 2015) - Seenaiah, Mallikanti; Jbara, Muhammad; Mali, Sachitanand M.; Brik, Ashraf
Abstract The chemical synthesis of a protein from four fragments or more applying native chemical ligation could be achieved stepwise, in one‐pot, convergently, or on a solid support. With the increasing demands of applying protein synthesis to highly complex targets, examining these approaches becomes essential to achieve highly efficient synthesis. Different chemical synthetic strategies are compared for the preparation of the H2B protein having different post‐translational modifications. The analogues include H2B that is ubiquitinated at Lys34, Lys120, glycosylated at Ser112, and doubly modified with ubiquitin and N‐acetylglucosamine. This study demonstrates that the applied convergent strategy for the synthesis of most of these complex targets was better than the one‐pot approach in terms of yield and purity. Some guidelines are offered for future synthetic endeavors of similar challenging proteins.